Neuroscience of Object Relations in Health and Disorder: A Proposal for an Integrative Model - Svrakic, Dragan M.; Zorumski, Charles F. (Frontiers in Psychology, 2021)
Recent advances in the neuroscience of episodic memory provide a framework to integrate object relations theory, a psychoanalytic model of mind development, with potential neural mechanisms. Object relations are primordial cognitive-affective units of the mind derived from survival- and safety-level experiences with caretakers during phase-sensitive periods of infancy and toddlerhood. Because these are learning experiences, their neural substrate likely involves memory, here affect-enhanced episodic memory. Inaugural object relations are encoded by the hippocampus-amygdala synaptic plasticity, and systems-consolidated by medial prefrontal cortex (mPFC). Self- and object-mental representations, extracted from these early experiences, are at first dichotomized by contradictory affects evoked by frustrating and rewarding interactions (“partial object relations”). Such affective dichotomization appears to be genetically hardwired the amygdala. Intrinsic propensity of mPFC to form schematic frameworks for episodic memories may pilot non-conscious integration of dichotomized mental representations in neonates and infants. With the emergence of working memory in toddlers, an activated self- and object-representation of a particular valence can be juxtaposed with its memorized opposites creating a balanced cognitive-affective frame (conscious “integration of object relations”). Specific events of object relations are forgotten but nevertheless profoundly influence the mental future of the individual, acting (i) as implicit schema-affect templates that regulate attentional priorities, relevance, and preferential assimilation of new information based on past experience, and (ii) as basic units of experience that are, under normal circumstances, integrated as attractors or “focal points” for interactive self-organization of functional brain networks that underlie the mind. A failure to achieve integrated object relations is predictive of poor adult emotional and social outcomes, including personality disorder. Cognitive, cellular-, and systems-neuroscience of episodic memory appear to support key postulates of object relations theory and help elucidate neural mechanisms of psychodynamic psychotherapy. Derived through the dual prism of psychoanalysis and neuroscience, the gained insights may offer new directions to enhance mental health and improve treatment of multiple forms of psychopathology.